Lactate/Albumin Ratio vs. NEWS-Lactate in Sepsis-Induced Acute Kidney Injury Prognosis; Comment on Le Xuan at al. Study - Jiang, Qing-Bao; Zhang, Guo-Ming (Archives of Academic Emergency Medicine, 2025)
A study by Le Xuan et al. suggested that the lactate/albumin ratio (LAR) may aid in predicting sepsis-associated acute kidney injury. However, overlapping receiver operating characteristic (ROC) curve confidence intervals, creatinine-only acute kidney injury (AKI) definitions, and single-point biomarker assessments limit interpretation. Given its single-centre retrospective design, broader validation with dynamic biomarkers and kidney-specific comparators is needed before the LAR can be integrated into sepsis risk stratification.